BACTERIOLOGICAL SUCCESSION DURING THE FERMENTATION OF OIL BEAN PURCHASED FROM EKEONUNWA MARKET IN OWERRI MUNICIPAL, IMO STATE (International Nexus Multidisciplinary Research Journal, 2026)
This study investigates the bacteriological succession during the fermentation of oil bean (Ugba) purchased from Ekeonunwa market, Owerri Municipal, Imo State, Nigeria. The aim was to monitor the microbial dynamics and identify the key bacteria involved in the fermentation process. Microbial populations, including Total Aerobic Plate Count (TAPC), Total Coliform Count (TCC), and Total Lactic Acid Bacteria Count (TLABC), were enumerated at 24, 48, and 72 hours of fermentation. Results showed a significant increase in TAPC (from 3.3 x 10⁶ CFU/ml at 24 hours to 8.9 x 10⁸ CFU/ml at 72 hours) and TLABC (from 3.1 x 10⁶ CFU/ml at 24 hours to 7.5 x 10⁸ CFU/ml at 72 hours), reflecting the growth of beneficial bacteria such as Lactobacillus spp. and Bacillus spp.. Conversely, the TCC decreased from 3.4 x 10⁴ CFU/ml to 1.1 x 10³ CFU/ml, indicating a reduction in non-beneficial or potentially pathogenic microorganisms. The study also identified bacterial species, including Lactobacillus spp., Bacillus spp., Micrococcus spp., Staphylococcus aureus, and Klebsiella spp., based on their colony morphology, microscopic features, and biochemical profiles. The microbial succession showed that Lactobacillus spp. and Bacillus spp. persisted throughout the fermentation period, while Micrococcus spp., Streptococcus spp., and Proteus spp. were more transient, with a decline by 72 hours. This succession highlights the dominance of beneficial microorganisms in the fermentation process, which is crucial for ensuring food safety, flavor development, and the microbiological stability of the final product. These findings emphasize the importance of monitoring microbial dynamics during fermentation to optimize conditions for producing high-quality and safe fermented products.